Bromo-protopine, a novel protopine derivative, alleviates tau pathology by activating chaperone-mediated autophagy for Alzheimer’s disease therapy - Sreenivasmurthy, Sravan Gopalkrishnashetty; Iyaswamy, Ashok; Krishnamoorthi, Senthilkumar; Reddi, Rambabu N.; Kammala, Ananth Kumar; Vasudevan, Karthick; Senapati, Sanjib; Zhu, Zhou; Su, Cheng-Fu; Liu, Jia; Guan, Xin-Jie; Chua, Ka-Kit; et al. (Frontiers in Molecular Biosciences, 2022)
Emerging evidence from Alzheimer’s disease (AD) patients suggests that reducing tau pathology can restore cognitive and memory loss. To reduce tau pathology, it is critical to find brain-permeable tau-degrading small molecules that are safe and effective. HDAC6 inhibition has long been considered a safe and effective therapy for tau pathology. Recently, we identified protopine as a dibenzazecine alkaloid with anti-HDAC6 and anti-AD activities. In this study, we synthesized and tested novel protopine derivatives for their pharmacological action against AD. Among them, bromo-protopine (PRO-Br) demonstrated a two-fold increase in anti-HDAC6 activity and improved anti-tau activities compared to the parent compound in both in vitro and in vivo AD models. Furthermore, molecular docking results showed that PRO-Br binds to HDAC6, with a ∆G value of -8.4 kcal/mol and an IC50 value of 1.51µM. In neuronal cell lines, PRO-Br reduced pathological tau by inducing chaperone-mediated autophagy (CMA). In 3xTg-AD and P301S tau mice models, PRO-Br specifically decreased the pathogenic hyperphosphorylated tau clumps and led to the restoration of memory functions. In addition, PRO-Br treatment promoted the clearance of pathogenic tau by enhancing the expression of molecular chaperones (HSC70) and lysosomal markers (LAMP2A) via CMA in AD models. Our data strongly suggest that administration of the brain-permeable protopine derivative PRO-Br, could be a viable anti-tau therapeutic strategy for AD.